Strangulated obturator hernia. - Mayol, Ricardo; Cazabán, Luis A (Cirugía del Uruguay, 1976)
A woman aged 82, who had been in pain for 3 hours and had manifest occlusion for the las 12 hours, was diagnosed as a case of stranguJated obturator hernia. Surgery was performed uslng local anesthesia. The strangulated area was necrosed and therefore resected. The patient died on the 8th. day.